Analisis Akuntabilitas dan Transparansi Laporan Keuangan pada Kelurahan Gundaling II Kecamatan Berastagi Kabupaten KARO - Ummu Huzaifah Br Purba; Nurlaila Nurlaila (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to analyze the level of accountability and transparency in the financial reports of Gundaling II Subdistrict and identify practices that influence community involvement in the supervision and use of public funds. Qualitative research methods are used by collecting data through analysis of financial reports, interviews with related parties, and direct observation of the financial management process. The results of the analysis show that although financial reports have generally been prepared well, there are still several areas where aspects of accountability and transparency need to be improved. These findings highlight the need to improve financial management procedures, use technology to improve transparency, and expand public participation in financial oversight. The implication of this research is the importance of implementing more transparent and accountable practices in local government financial management in order to increase community involvement and trust in the use of public funds.